Out of oz eaudiobook - Maguire, Gregory (Wicked Years, 2011)
New York Times best-selling author Gregory Maguire created a worldwide sensation with Wicked, the history of Elphaba, the Wicked Witch of the West. Maguire's chronicles of the land of Oz continue in the series' fourth and final volume, Out of Oz. War looms as the Emerald City is poised to invade Munchkin Land. Elphaba's granddaughter Rain is all grown and ready to assume her legacy. Meanwhile, a familiar visitor from Kansas arrives in Oz.